Development and performance of the public real estate investment sector in Finland - Falkenbach, Heidi; Niskanen, Jaakko; Kiehelä, Sami (International Journal of Strategic Property Management, 2013)
The article studies the development of the public real estate equity sector. The paper describes and analyses the legislative development regarding the sector and the vehicles provided. It discusses the past development of public commercial real estate equity investments in Finland and their role as a market participant. In addition, the paper analyses the historical performance of the sector.First Publish Online: 23 Sep 2013